Analalisis Faktor-Faktor Yang Mempengaruhi Kualitas Informasi Akuntansi Pada Rumah Sakit. (Studi empiris pada Rumah Sakit PKU Muhammadiyah se Eks-karisidenan Surakarta). - Rusnanto, Galeh; , Dr. Noer Sasongko, SE, M.Si, Ak (2016)
The purpose of this research to analyze the factors which influence the accountancy quality information in PKU Muhammadiyah Hospital Eks-karisidenan Surakarta. As regard to the factors are relevant, reliable, complete, on time, understandable and can be verified. The method which used to take the sample in this research by non probability sampling conveniencce. The data which used in this research by using the primary data. The removal technique of the reseach data is taken directly by questionner. The analysis tools which used in this research shows that the information is relevant, reliable, complete, on time, , understandable and can be verified which influental of the significant statiscally of the informtion quality in the hospital Key word : relevant, reliable, complete, on time, understandable and can be verified.